Assessing socio-demographic factors affecting fatigue level among community-dwelling older people / Nur Sakinah Baharudin ... [et al.] - Baharudin, Nur Sakinah; Talib, Siti Salwa; Mohamad Nor, Nur Farahsyahirah; Azri, Muhammad Azwan; Ahmad Ainuddin, Husna; Che Daud, Ahmad Zamir (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
This study examines the link between fatigue level and socio-demographic profiles of community-dwelling older people attending the Elderly Activity Center. The influence of medical conditions (Type-2 diabetes, hypertension, heart disease, hyperlipidemia, and asthma) on fatigue levels were also explored. A cross-sectional study with purposive sampling was conducted on 180 community-dwelling older people aged 65 years and above in Selangor. Based on statistical analyses, it was found that Physical Fatigue has the highest fatigue level among community-dwelling older people. There was a significant difference between age and Reduced Motivation, education level and Reduced Activity, and the number of illnesses and General Fatigue. Type 2 diabetes mellitus added significantly with Mental Fatigue, and asthma was significant with all fatigue scales except Mental Fatigue. The study suggested that physical fatigue is the most prominent among older people compared to other fatigue dimensions and has some association with socio-demographic factors. Therefore, effective fatigue management considering all cohabiting factors should be encouraged in treating fatigue among community-dwelling older people